THE ROLE OF NOZIMAXONIM’S ENLIGHTENMENT IDEAS AND PUBLICISTIC ACTIVITY IN THE LEGACY OF JADID WOMEN - Ergashova Mehriniso Husniddin kizi (International Journal of Literature and Language Studies, 2026)
This article examines the role of Nozimaxonim in the legacy of Jadid women and her contribution to the development of enlightenment ideas in the Uzbek press. The study analyzes her literary and publicistic activity as an important example of women’s participation in social thought during the period of national awakening. Special attention is paid to women’s literacy, education, cultural renewal, and the formation of women’s voices in public discourse. The article emphasizes that Nozimaxonim’s legacy is significant for understanding the early development of Uzbek women’s journalism and the role of enlightened women in social and spiritual progress.